Effective handling of nonlinear distortions in CO-OFDM using affinity propagation clustering - Wei, Jinlong; Giacoumidis, Elias; Zhou, Ji; Jarajreh, Mutsam A.; Li, Shi; Aldaya, Ivan; Lu, Yandong; Tsokanos, Athanasios; Richter, Andre (Optica Publishing Group, 2022)
We experimentally demonstrate a system-agnostic and training-data-free nonlinearity compensator, using affinity propagation (AP) clustering in single- and multi-channel coherent optical OFDM (CO-OFDM) for up to 3200 km transmission. We show that AP outperforms benchmark deterministic and clustering algorithms by effectively tackling stochastic nonlinear distortions and inter-channel nonlinearities. AP offers up to almost 4 dB power margin extension over linear equalization in single-channel 16-quadrature amplitude-modulated CO-OFDM and a 1.4 dB increase in Q-factor over digital back-propagation in multi-channel quaternary phase-shift keying CO-OFDM. Simulated results indicate transparency to higher modulation format orders and better efficiency when a multi-carrier structure is considered.